2015
DOI: 10.1109/jsen.2015.2444798
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Single Thermopile SOI CMOS MEMS Thermal Wall Shear Stress Sensor

Abstract: In this paper, we present a novel silicon-on-insulator (SOI) complementary metal-oxidesemiconductor (CMOS) microelectromechanical-system thermal wall shear stress sensor based on a tungsten hot-wire and a single thermopile. Devices were fabricated using a commercial 1-µm SOI-CMOS process followed by a deep reactive ion etching back-etch step to release a silicon dioxide membrane, which mechanically supports and thermally isolates heating and sensing elements. The sensors show an electrothermal transduction eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Packaged multidirectional flow sensors were then calibrated for multidirectional wall shear stress (τ) measurement as described in [6] in both constant current (CC) and constant temperature (CT) mode. In Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Packaged multidirectional flow sensors were then calibrated for multidirectional wall shear stress (τ) measurement as described in [6] in both constant current (CC) and constant temperature (CT) mode. In Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Several dies (1.6 mm × 1.6 mm in size) were subsequently wedge bonded in-house onto commercially available ceramic pin grid array (CPGA) packages as described in [6]. …”
Section: Sensor Design Fabrication and Packagingmentioning
confidence: 99%
“…In the current set-up, four thermopiles were used: North (TPN1 in Figure 4), South (TPS1), East (TPE1) and West (TPW1). De Luca et al (2015a) showed that the outputs from these sensors can be calibrated for shear stress τ using the equation:…”
Section: Funding Sourcesmentioning
confidence: 99%
“…Time-of-flight (TOF) sensors measure the time elapsed between the injection and the detection of a heat pulse [ 48 ]. This configuration consists of an upstream heater, which generates a heat pulse and transfers it to the surrounding fluid flow and at least one temperature sensor, which acts as a downstream sensor as shown in Figure 2 d. The underlying fundamentals of TOF sensing have been intensively covered in [ 49 ].…”
Section: Thermal Flow Sensors and Their Operationmentioning
confidence: 99%